Strategies and open questions in solid-phase protein chemical synthesis. (October 2020) - Agouridas, Vangelis; Diemer, Vincent; Melnyk, Oleg
Abstract: The review gives a large overview of the strategies used for protein synthesis by chemoselective peptide segment ligation on a solid support. It discusses also important aspects that remain to be explored to further develop the technology such as the role of the solid support on reactant diffusion rates, on ligation kinetics, as well as on the folding and functionality of the proteins attached to the solid support. Graphical abstract: Image 1